VARIABILITY OF SOME PRODUCTIVE TRAITS OF TWO-ROW SPRING BARLEY IN THE CONDITIONS OF ARDS TURDA - Emilia Ancuța Boantă; Ioana Porumb; Florin Russu; Emanuela Filip; Leon Muntean; Andreea Daniela Ona (Agricultura, 2019)
Furthermore to additive action of polygenes, in heredity of quantitative traits, other types of intra-allelic (dominance and recessiveness) and inter-allelic (epistasis) interactions are also involved, all this ultimately leading to a complex heredity of these traits. Although it was initially believed that the constitutive elements of yield had a simpler heredity and that the decomposition of production by these elements would lead to a more efficient selection for this trait, after extensive research, it was concluded that yield elements also had a complex heredity. Regarding grains weight/ear, most performing were the native cultivars Turdana and Aura with statistical differences compared to the control (the average of the two experimental years), 0.38 g, highly significant positive and 0.14g, significant positive. As expected due to the close positive correlation between the grains weight/ear and the number of grains, Turdeana and Aura cultivars are also leaders for the number of grains/ear.